Evaluación de la adición de los residuos de la planta de quinua (Chenopodium quinoa) en la alimentación de cuyes (Cavia porcellus) en la etapa de crecimiento y engorde en el cantón Mejía, barrio La Moya - Fonseca Paltan, Sandra Elizabeth (2015)
This research was developed in Pichincha province, Mejia Canton, Aloasi Parish, La Moya neighborhood in order to evaluate the addition of waste of quinoa plant (Chenopodium quinoa) in feeding, growing and fattening stage of guinea pigs to determine production parameters. For this investigation 40 guinea pigs weaned from Peru line males which were divided into 4 groups of 10 animals 3 treatments (T1 10% waste quinoa + alfalfa, T2 20% waste quinoa + alfalfa, T3 30% waste quinoa + alfalfa) and a witness treatment (T4 only alfalfa) were used….